Relação do letramento funcional em saúde e adesão ao tratamento com anticoagulantes orais em pacientes com fibrilação atrial - Frederico Bartolazzi (2020)
Introduction: Atrial fibrillation (AF) is the most frequent arrhythmia in clinical practice, being an important public health problem around the world. The use of oral anticoagulants (OAC) is useful to prevent cardioembolic events in patients at increased risk for thromboembolism. Patient adherence is essential to achieve effectiveness and safety of drug therapy. Health literacy (HL) is one of the major obstacles, which can impact on adherence to drug therapy. Aim: To investigate the relationship between HL and adherence to treatment with OAC in patients with FA. Methods: An observational, cross-sectional study was conducted in a public cardiology clinic located in Curvelo, Minas Gerais. Patients were recruited between February and September, 2019. Inclusion criteria were: age ≥18 years, AF diagnosis by electrocardiogram and/or holter 24 hours, previous indication of OAC, use of OAC of the class of vitamin K inhibitors or direct anticoagulants. Data collection involved the review of medical records and patient interview. We collected sociodemographic and clinical data. Validated instruments were used to measure the HL (Short Assessment of Health Literacy for Portuguese speaking Adults, validated for the Brazilian Portuguese language) and for adherence to drug therapy (Treatment Adherence Measure). This study was approved by the Research Ethics Committee of the Universidade Federal de Minas Gerais (CAAE:00193018.9.0000.5149). All participants signed an informed consent form. Results: Overall, 100 patients were included in the study, presenting the mean age of 68.8±13,8 years old and 54% of women. Most patients (74%) presented completed elementary school. The average family monthly income was US$ 362.49. A total of 69% of participants were taking chronically ≥five drugs. HL was classified as inadequate for 79% of patients and 66% of them were considered non-adherent to drug therapy with OAC. There was no statistically significant relationship between inadequate HL and non-adherence to drug therapy with OAC (Odds ratio (OR) 1,48; Confidence interval (CI) 95% 0,47-4,61; p=0,49). Conclusions: We identified high rates of inadequate HL and non-adherence to drug therapy with OAC, however this relationship did not present statistical association. Our results suggest the need of further studies to investigate factors associated with non-adherence to drug therapy with OAC in vulnerable populations and the design of strategies for its improvement in public health.